Building Loyalty in Islamic Banking: How Brand Trust and Mobile Banking Quality Drive Customer Satisfaction and Retention - Navilah Laila Wardani; Harun Alrasyid; Nurhidayah (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of brand trust and mobile banking service quality on customer loyalty through customer satisfaction in the islamic banking industry in indonesia. A quantitative research method was employed with a sample of 230 respondents, consisting of bank syariah indonesia (BSI) customers in the malang raya area. Data were collected using a likert-scale questionnaire and analyzed using the partial least squares structural equation modeling (PLS-SEM) method with the help of smartpls 4 software. The results indicate that both brand trust and mobile banking service quality have a positive and significant effect on customer satisfaction, which in turn serves as a strong mediating variable in the relationship. Furthermore, mobile banking service quality has a significant positive effect on customer loyalty, as does customer satisfaction. Brand trust and mobile banking service quality also significantly influence customer loyalty through customer satisfaction as a mediating variable. These findings highlight the crucial role of customer satisfaction in building customer loyalty. It is evident that both brand trust and the quality of mobile banking services enhance satisfaction, which ultimately drives loyalty. Therefore, islamic banks need to strengthen customer trust and improve the quality of their digital services to retain their customers.